Left ventricular pressure/volume relationship in coronary artery disease - Iskandrian, Abdulmassih S.; Heo, Jaekyeong (The American heart journal, 1986)
This study examined the changes during exercise in LV EF and P V relationship (systolic blood pressure/end-systolic volume index ratio) in 287 patients. Normal range (mean ± standard deviation) for exercise EF, exercise P V , and the changes from rest to exercise (Δ) in EF and P V were established in 51 subjects with <1% probability of CAD. The results were compared to those obtained in 53 patients with normal coronary angiograms and 183 patients with angiographically proven CAD. Abnormality in either ΔEF or percent ΔP V were observed in 76% of the patients with one-vessel disease and in 91% of patients with multivessel disease. Abnormalities in either ΔEF or percent ΔP V were more common than ΔEF alone in the total CAD group and in subgroups stratified according to the resting EF, extent of CAD, and adequacy of exercise end points. Similar results were obtained when absolute exercise EF or exercise P V were used. Abnormalities in the percent ΔP V or ΔEF were also seen in 26 of the 53 patients with normal coronary angiograms. Thus, abnormalities in the P V relationship or EF during exercise are more common than abnormalities in the EF alone. Relative and absolute measurements provide similar results.